Communication of Political Parties (Phenomenology Study of Political Communication of Da’wah DPD Prosperous Justice Party in Cianjur Regency) - Cecep Suryana , Muhamad Selpan Muharam Shidiq (Migration Letters, 2024)
This study aims to assess the efficacy of the Prosperous Justice Party’s (PKS) political communication process, examining the elements of communicator, message, channel, goals, and objectives. In addition, a subjective paradigm is adopted through a phenomenological approach with qualitative methods, and data collection techniques include interviews, observation, and documentation. The results show that the PKS DPD propaganda communication pattern in Cianjur Regency uses several methods or patterns. The party uses interpersonal communication, enhancing direct engagement between PKS cadres and the community through house-to-house interactions. In this context, the two patterns of da’wah political communication are through the three pillars of the Cianjur Baru flagship program, namely the economic, agricultural, and religious pillars. The interpersonal communication strategy carried out by PKS cadres is a form of direct interaction with the community through the door-to-door method. The strategy includes the process of sending and receiving messages between two or more people in a small group with some effects and instant feedback.